Providensia Allah bagi Kebahagiaan Rumah Tangga Kristen - Nurlela Syafrian Oematan (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
The Christian home is like a vast ocean to be crossed. On the journey across the vast ocean, sometimes you will experience calm, but often it will be turbulent, through typhoons, filled with rocks and icebergs. However, many arks of Christian households are sunk or divorced because of hitting rocks or complicated problems, and innocent children remain as victims. This happens because of the lack of preparation that is carried out before entering the household or also because of the lack of preparation that is carried out before entering the household or also because of a lack of vigilance in living a household life, it is necessary to provide God's providence in the household. Therefore, the author uses an inductive method in the form of literary studies as the theological basis for God's providence in marriage for the happiness of Christian households.